El Excentrico, 1949-12-01 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, CA, 2023)
December 1949 [Diciembre de 1949]. Ano 1, No. 6. Cover contains photos of veterans of Latin origin commorating the Day of Arms, while being acompanied by allegorical chariots.